Genetic Algorithm Based Optimal Design of a PlD Controller for Trajectory Tracking of a Mobile Robot - Abdalla, Turki Y.; AI_Duboni, Seaar J. (Basrah Journal for Engineering Sciences, 2010)
This paper deals with the modeling and control strategics of the motion of wheeled mobile robot. The model of the mobile robot has two driving wheels and the azimuth and velocity are dependently controlled by two PID controllers. The PID controller is one of the earliest and famous industrial controllers. It has many advantages: It is economic, simple easy to be tuned and robu.~t. The tuning of these controllers is governed by system nonlinearities and continuous parameter variations. lbis paper deals with the optimal design of a PID controller for path tracking of mobile robot by using genetic algorithms (GA). The designed controller is tested for different paths.